RNA Transcription by the Virion Polymerases of Five Rhabdoviruses - Chang, S. H. (1974)
The presence of a virion-associated RNA-dependent RNA polymerase in five serologically distinct rhabdovirus isolates (vesicular stomatitis virus [VSV] Indiana, VSV New Jersey, Cocal, Chandipura, and Piry viruses) has been demonstrated. The enzyme for each virus has been shown to be a transcriptase capable of synthesizing in vitro RNA which is complementary to the viral genome. By sequence analyses it has been shown that, for each rhabdovirus, transcription is multiply initiated with specific 5′ nucleotide sequences. The results indicate that, for all five viruses, the initiation of transcription involves similar sequences (e.g., pppApCpGp..., pppGpCp..., and possibly one or two other sequences), suggesting relatedness and some genome conservation among these viruses.